White Matter Damage in the Cholinergic System Contributes to Cognitive Impairment in Subcortical Vascular Cognitive Impairment, No Dementia - Liu, Qing; Zhu, Zude; Teipel, Stefan J.; Yang, Jianwei; Xing, Yi; Tang, Yi; Jia, Jianping (Frontiers in Aging Neuroscience, 2017)
Cholinergic deficiency has been implicated in the pathogenesis of vascular cognitive impairment (VCI), but the extent of involvement and underlying mechanism remain unclear. In this study, targeting the early stage of VCI, we determined regional atrophy within the basal forebrain and deficiency in cholinergic pathways in 25 patients with vascular cognitive impairment no dementia (VCIND) compared to 24 healthy elderly subjects. By applying stereotaxic cytoarchitectonic maps of the nucleus basalis of Meynert (NbM), no significant atrophy was identified in VCIND. Using probabilistic tractography analysis, our study tracked the two major white matter tracks which map to cholinergic pathways. We identified significantly lower fractional anisotropy (FA) in VCIND. Mediation analysis demonstrated that FA in the tracked pathways could fully account for the executive dysfunction, and partly mediate the memory and global cognition impairment. Our study suggests that the fibers mapped to the cholinergic pathways, but not the NbM, are significantly impaired in VCIND. MRI-based in vivo tracking of cholinergic pathways together with NbM measurement may become a valuable in vivo marker for evaluating the cholinergic system in cognitive disorders.